An Instrument for Merging of Bibliographic Databases; 15th ACM/IEEE-CS Joint Conference on Digital Libraries - Knyazeva A. A. Anna Anatolievna; Kolobov O. S.; Tatarsky F. E.; Turchanovsky I. Yu. Igor Yurjevich (2015, 2015)
Title screen